Factors of Changes in Livelihood Choices for Generation Z and Impact on Farmer’s Families - Oktav Nugraha, Saka Mahardika; Priyanto, Agustinus Sugeng; Alimi, Moh Yasir (Universitas Negeri Semarang, 2020)
The purpose of this study is to determine the causes and effects of changes livelihood choices for generation Z children and the impact of social changes in farmer families in Desa Karangmalang. This research used qualitative with the form of case studies. The data is collected through observation, interviews, and documents. The collected data will be analyzed using qualitative analysis, namely by describing the results of research in the form of words or sentences so that the researchers describe in depth the results of the research in accordance with the actual conditions that occurred in the field. The research targets were generation Z children and farmer families. The results showed that the factors of changes in livelihood choices was motivated by the knowledge of generation Z children about farmers, the economic value of the farming family, and the social status of the farmer families for generation Z children. These factors have influenced the social changes of generation Z children to choose livelihoods other than farmers.